Effect of surface nanocrystallization on low-temperature gas carburization for AISI 316L austenitic stainless steel. (May 2020) - Liu, Zhe; Peng, Yawei; Chen, Chaoming; Gong, Jianming; Jiang, Yong
Abstract: In this paper, the effect of surface nanocrystallization on low-temperature gas carburization (LTGC) for AISI316L austenitic stainless steel was studied. Surface ultrasonic rolling processing (SURP) was used to prepare the nanostructured surface layers and then the un-SURP and SURP specimens were treated by LTGC at 430 and 470 for 10 h, 20 h and 30 h. After the SURP treatment, the thickness of plastic deformation layer was about 350 μm and the compressive residual stress generated on the surface was −857.67 ± 55.54 MPa. In addition, the surface roughness decreased obviously. The SURP treatment has a negative effect on the thickness of the carburized layer but it significantly increases the carbon concentration, nanohardness, elastic modulus and compressive residual stress of the outer surface of the carburized layer. However, these parameters then rapidly decreased along the depth of the carburized layer. Both SURP and LTGC could significantly strengthen the surface of AISI316L steel and the combination of the two would achieve better surface properties. Highlights: The comparison of properities for the un-SURP and SURP specimens is carried out after low-temperature gas carburization with different carburizing time and temperature. The results are different from some similar studies and the reasons are discussed. Nanoindentation tester was used to obtain load-displacement curves and calculate the profiles of nanohardness and elastic modulus along the depth of the carburized layer.